Biomarkers of Oxidative Stress in Diabetic Microvascular Complications Review Article - Sarah Hashim Mhaibes; Shatha H. Ali (Iraqi Journal of Pharmaceutical Sciences, 2024)
Reactive oxygen species (ROS) are produced as a result of biochemical processes that are not in balance with the body's antioxidant defense mechanism. This metabolic dysfunction is referred to the oxidative stress (OS). Metabolic dysfunction-associated diseases are affected by changes in the redox balance. It is now widely recognized that oxidative stress significantly affects diabetes mellitus (DM), particularly type 2 diabetes. The biochemical changes associated with DM could disturb the oxidative milieu, leading to several microvascular complications in diabetic patients. Thus, DM is a perfect disease to explore the harmful consequences of oxidative stress and how to treat it. Oxidative stress triggered by hyperglycemia is an important contributor to the effects of diabetic microvascular diseases. Uncontrolled hyperglycemia carried by deficiencies in insulin secretion or action produces a number of problems, such as peripheral vascular disorders, nephropathy, neuropathy, retinopathy, increased morbidity and/or mortality, as well as the incidence of diabetes mellitus (DM) are rising globally. The development and progression of diabetic problems are strongly correlated with reactive oxygen species and oxidative stress, according to a wide body of research. This review aims to explore various markers of oxidative stress and the role of ROS in the pathogenesis and progression of late diabetic microvascular complications.